IDENTIFIKASI BAKTERI VIBRIO SP PADA UDANG WINDU (Penaeus Monodon) DI TAMBAK TRADISIONAL KOTA TARAKAN - Gusman, Ery; ., Firman (Jurnal Harpodon Borneo, 2012)
The purpose of this research is to identification the availability of Vibrio sp. Bacteria on black tiger shrimp (Penaeus monodon) in Tarakan ponds. Sample was used in this research are shrimp taken from three location of ponds. Shrimp collected On each location of ponds,. Data was collected showing in descriptive form that is analyzing Vibrio sp. bacteria emerge in black tiger. If isolation of bacteria grown on 1,5 % TSA medium and then purified on same medium. Vibrio identification has done by several test, they are Gram test, catalase test, oxidase test, motility test, O/F test, TSIA and glucose test. Data of identification arrange on table, then analyzed by described it based water parameter such are temperature, Dissolved Oxygen (DO), pH, Salinity and Ammonia. This research result shows the availability of Vibrio sp. on each ponds shrimp. Keywords: Vibrio sp., Tarakan, Ponds, Penaeus Monodon.